Analysis of the Effect of Lemon Aromatherapy Inhalation on Morning Sickness in Pregnant Women at Puskesmas Tiley - Sutria Tomagola; Retno Dewi Prisusanti (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Emesis gravidarum, or nausea and vomiting during early pregnancy, is a common condition affecting the health and comfort of first-trimester pregnant women. Persistent symptoms can lead to dehydration, electrolyte imbalance, reduced nutrient intake, and psychological distress, potentially affecting both maternal and fetal health. Although pharmacological treatments are available, many pregnant women prefer non-pharmacological approaches due to concerns about fetal safety. Aromatherapy, using essential oils such as lemon, peppermint, and lavender, has emerged as a complementary therapy that may reduce nausea and vomiting through olfactory stimulation and autonomic nervous system modulation. This study aimed to examine the effect of aromatherapy on reducing emesis gravidarum in first-trimester pregnant women at Puskesmas Pagatan. A quasi-experimental design with pretest-posttest control group was conducted, involving 40 participants divided into an intervention group (n=20) and a control group (n=20) using purposive sampling. The intervention group received lemon essential oil inhalation twice daily for seven consecutive days, while the control group continued standard antenatal care. Data were collected using the Visual Analog Scale (VAS) for nausea severity and a structured diary for vomiting frequency. Results showed that the intervention group experienced a significant reduction in nausea severity (pretest mean 6.8 ± 1.2, posttest mean 3.2 ± 1.0, p < 0.001) and vomiting frequency (pretest mean 5.2 ± 1.0, posttest mean 2.1 ± 0.9, p < 0.001). In contrast, the control group showed minimal, non-significant changes. These findings indicate that aromatherapy is an effective, safe, and culturally acceptable non-pharmacological intervention for managing emesis gravidarum. The study concludes that integrating aromatherapy into routine antenatal care can improve maternal comfort, adherence to nutritional intake, and overall well-being in first-trimester pregnancies, supporting holistic prenatal care practices.